Penggunaan Buku Saku untuk Meningkatkan Keterampilan Literasi Siswa di SMA Negeri 1 Rantau Selatan - Davit Ritonga; Aulia Safira; Patricia Sinurat (Politeknik Kampar, 2025)
This research is motivated by the lack of interest in reading literacy of students at SMA Negeri 1 Rantau Selatan with existing reading books. Therefore, the author made an innovation in using small, simple and easy-to-carry pocket books to improve student literacy. The purpose of this study is to increase reading interest and literacy skills of class X students at SMA Negeri 1 Rantau Selatan through the creation of pocket books that are relevant to student needs, and can improve student understanding of subject matter through interesting media. The research method used is a quantitative research method used to analyze data by conducting interviews and distributing questionnaires to class X student respondents regarding the benefits of learning media for pocket books for PPKn subjects with the material of the Unitary State of the Republic of Indonesia in improving literacy skills. The results of the study showed that the implementation of PUSAKI in class X of SMA Negeri 1 Rantau Selatan showed a positive impact on student literacy skills.